2013
DOI: 10.1210/jc.2013-1173
|View full text |Cite
|
Sign up to set email alerts
|

Steroid Hormone Profiles in Prepubertal Obese Children Before and After Weight Loss

Abstract: In obese prepubertal children, the increased androgens, mineralocorticoid precursors, and glucocorticoids were responsive to weight loss in contrast to DHEAS, suggesting that DHEAS does not seem to be regulated by changes in body mass index.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
56
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(66 citation statements)
references
References 38 publications
8
56
1
1
Order By: Relevance
“…Adipose tissue distribution is heavily influenced by sex, with sex-related patterns becoming apparent during puberty. However, in obese female children, a BMI-related increase in androgens [24,25] may favour central adiposity. In addition, obese female children have a greater degree of obesity-induced insulin resistance [26], and the compensatory hyperinsulinaemia may further facilitate accumulation of visceral fat [27].…”
Section: Discussionmentioning
confidence: 99%
“…Adipose tissue distribution is heavily influenced by sex, with sex-related patterns becoming apparent during puberty. However, in obese female children, a BMI-related increase in androgens [24,25] may favour central adiposity. In addition, obese female children have a greater degree of obesity-induced insulin resistance [26], and the compensatory hyperinsulinaemia may further facilitate accumulation of visceral fat [27].…”
Section: Discussionmentioning
confidence: 99%
“…Production of stress hormones was found to be higher in obese children 18 . Earlier studies reported positive correlation between obesity and stress in children and adolescents 19,20 . In contrast, in adults, there exists contradictory results regarding association of obesity and stress 21,22 .…”
Section: Discussionmentioning
confidence: 86%
“…All undergraduate MBBS students in the age group [18][19][20][21][22][23][24][25] years studying in Saveetha Medical College 2. Willing participants 3.…”
Section: Inclusion Criteriamentioning
confidence: 99%
“…Usually, for the hormonal assessment of CAH, several steroids have to be considered as a pattern in parallel, e.g., 17-hydroxyprogesterone, androstenedione, cortisol in 21OHD [28]. We here established MoM cutoffs for “diagnostic single-steroid MoMs” predicting 21OHD (17-hydroxyprogesterone > 3.78; 21-deoxycortisol > 12.28) and 11OHD (11-deoxycortisol > 13.18).…”
Section: Discussionmentioning
confidence: 99%
“…The ACC patients had originally been analyzed for routine diagnostic purposes. The hormone concentration data of the obesity group ( n = 40: 20 males, 20 females; aged 6.4 to 10.6 years) has been published previously by Reinehr et al [28]. …”
Section: Methodsmentioning
confidence: 99%